2013
DOI: 10.1351/pac-con-12-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Inherent dynamical preferences in carbocation rearrangements leading to terpene natural products

Abstract: An introduction to the application of quantum chemical dynamics calculations to mechanistic problems in the field of terpene biosynthesis is provided. A bare bones introduction to the fundamentals of chemical dynamics is followed by a brief account of previous applications to terpene-forming carbocation reactions, a discussion of questions in this field that dynamics calculations may help answer, and a description of current problems to which dynamics calculations are being applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…For most systems, this is a reasonable assumption, but careful consideration of any chemical steps in the reaction preceding the transition state from which trajectories are initiated should be made, since any dynamical effects preceding the transition state would be neglected and would have to be treated separately if of interest. Studies involving trajectories initiated from minima and transition states have both been carried out on carbocations [ 25 ] and examples of each are described below. While many different quantum chemical methods can be used to carry out trajectory calculations, standard density functional theory (DFT) approaches are most commonly used [ 35 – 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…For most systems, this is a reasonable assumption, but careful consideration of any chemical steps in the reaction preceding the transition state from which trajectories are initiated should be made, since any dynamical effects preceding the transition state would be neglected and would have to be treated separately if of interest. Studies involving trajectories initiated from minima and transition states have both been carried out on carbocations [ 25 ] and examples of each are described below. While many different quantum chemical methods can be used to carry out trajectory calculations, standard density functional theory (DFT) approaches are most commonly used [ 35 – 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…Even when the branching of reaction paths does occur at a local PES minimum, classical molecular dynamics (MD) simulations have shown that one cannot rely on the validity of the statistical approximation for gas-phase reactions. 15,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The Figure 1. Schematic depiction of a PES with a bifurcating reaction path.…”
Section: Changes In the Code Of Behaviormentioning
confidence: 99%
“…Although a straightforward stationary point analysis ( i.e. , comparison of competing TSSs) is not possible for such scenarios, product ratios can be predicted via dynamics simulations in which multiple trajectories are initiated in the region of the ambimodal TSS by giving the optimized TSS a random distribution of potential and kinetic energy, then propagated forward and backward in time; product ratios are predicted based on the frequency of formation of each product 3…”
Section: Introductionmentioning
confidence: 99%